KNOWLEDGE MANAGEMENT, ENTREPRENEURIAL COMPETENCIES AND ORGANIZATIONAL DEVELOPMENT IN MICRO AND SMALL ENTERPRISES IN RURAL REGIONS IN THE STATE OF YUCATAN, MEXICO - Barroso Tanoira, Francisco Gerardo; Santos Valencia, Raul Alberto (European Scientific Journal, ESJ, 2014)
Globalization today motivates companies to change according to market needs and for adapting to their environment, so it is necessary for them to manage their knowledge efficiently reinventing, innovating and implementing new product and service strategies, incorporating them to new business models and challenges. This is why the relation among knowledge management, entrepreneurial development and organizational performance becomes more important. In rural regions of the State of Yucatan, in the South East of Mexico, natural environment conditions, culture and the way of life could become barriers for entrepreneur formation and hence, for the development of micro and small business firms. Knowing the way for managing knowledge, the entrepreneurial competencies of micro and small entrepreneurs, as well as their organizational performance, will allow Government, universities, business chambers and private investors, design and implement strategies for contributing to a better development of such companies, improving the quality of life of people in such regions